2012
DOI: 10.5089/9781475503494.001
|View full text |Cite
|
Sign up to set email alerts
|

Capital Inflows, Financial Development, and Domestic Investment: Determinants and Inter-Relationships

Abstract: We examine determinants of, and interactions between, capital inflows, financial development, and domestic investment in developing countries during 2001-07, a period of surging global liquidity and low interest rates. Reductions in the global price of risk and in domestic borrowing costs were the main contributors to the increase over time in net capital inflows and domestic credit. However, the large cross-country differences in domestic and international finance are best explained by fundamentals such as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…From a study of 50 African countries, political stability, control of corruption, and regulatory quality were found to have a significant impact on FDI inflows (Gangi and Abdrazak, 2012), whereas low regulatory law and political stability enhanced FDI inflows of 45 developing countries in Africa, Asia, and Latin America (Bissoon, 2011). A study of 103 countries between 2001-2007 revealed that good governance indicators showed mixed results in both effect and significance (Spatafora and Luca, 2012), which is in line with the result from a study of 124 countries between 1996-2009 (Gordon et al, 2012). From 1995-1997, voice and accountability, government effectiveness, regulation, and control of corruption had significant positive effects on 115 developing and developed countries (Globerman and Shapiro, 2003).…”
Section: Linkages Between Good Governance and Fdi Inflowssupporting
confidence: 75%
“…From a study of 50 African countries, political stability, control of corruption, and regulatory quality were found to have a significant impact on FDI inflows (Gangi and Abdrazak, 2012), whereas low regulatory law and political stability enhanced FDI inflows of 45 developing countries in Africa, Asia, and Latin America (Bissoon, 2011). A study of 103 countries between 2001-2007 revealed that good governance indicators showed mixed results in both effect and significance (Spatafora and Luca, 2012), which is in line with the result from a study of 124 countries between 1996-2009 (Gordon et al, 2012). From 1995-1997, voice and accountability, government effectiveness, regulation, and control of corruption had significant positive effects on 115 developing and developed countries (Globerman and Shapiro, 2003).…”
Section: Linkages Between Good Governance and Fdi Inflowssupporting
confidence: 75%
“…Table 4.2 lists that Kar (1983); Zebib and Muoghalu (1997) Haroon and Nasr (2011) Pakistan Total amount of debt servicing Lim and Kim (2011) 23 Developing countries Sum of the gross stocks of foreign assets and liabilities as a share of GDP Spatafora and Luca (2012) Net equity inflows (percent of GDP) Net debt inflows (percent of GDP) Net bond inflows (percent of GDP) Law and Azman-Saini (2013) Malaysia FDI inflows Portfolio inflows (Naghavi and Lau, 2014) 27 Emerging markets Sum of equity in-and outflows as a share of GDP: annual capital flows Saadaoui (2015) Gross foreign assets as sum of foreign assets and liabilities…”
Section: Financial Openness (De Facto)mentioning
confidence: 99%
“…Developing economies face the problem of low savings and low rate of investment therefore require development of sound financial system to overshadow the quantity of investment as a driver of growth. Development of financial sector may solve this issue as it is often said that the stronger and better financial system can lift growth by boosting the aggregate savings and investment rate, which results into speeding up the accumulation of physical capital (Mundial, 2013a, b; Luca and Spatafora, 2012; Sakyi et al , 2016; Iheonu et al , 2020). Efficient financial intermediaries ensure that the scarce financial resources are channelled to the highest priority economic alternatives outcomes and investments (Iheonu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%